DRD4 alleviates acute kidney injury by suppressing ISG15/NOX4 axis-associated oxidative stress - Yue Gao; Xun Lu; Guangyuan Zhang; Chunhui Liu; Si Sun; Weipu Mao; Guiya Jiang; Yu Zhou; Nieke Zhang; Shuchun Tao; Ming Chen; Shuqiu Chen; et al. (Redox Biology, 2024)
Acute kidney injury (AKI) is a life-threatening health condition associated with increasing morbidity and mortality. Despite extensive research on the mechanisms underlying AKI, effective clinical tools for prediction and treatment remain scarce. Oxidative stress and mitochondrial damage play a critical role in AKI and dopamine D4 receptor (DRD4) has been confirmed to be associated with oxidative stress. In this study, we hypothesized that DRD4 could attenuate AKI through its antioxidative and antiapoptotic effects. In vivo, DRD4 was remarkably decreased in the kidneys of mice subjected to ischemia/reperfusion injury (IRI) or cisplatin treatment. Notably, DRD4 significantly attenuated nephrotoxicity by suppressing oxidative stress and enhancing mitochondrial bioenergetics through the downregulation of reactive oxygen species (ROS) generation and NADPH oxidase 4 (NOX4) expression. In vitro, DRD4 demonstrated the ability to ameliorate oxidative stress-induced apoptosis in HK-2 cells subjected to hypoxia/reoxygenation- or cisplatin treatment. Transcriptome sequencing revealed that, mechanistically, DRD4 reduced the expression of its downstream target, interferon-stimulated gene 15 (ISG15), suppressing NOX4 ISGylation, enhancing the ubiquitination of NOX4, leading to its degradation, and ultimately counteracting oxidative stress-induced AKI. Altogether, these findings underscore the significance of DRD4 in AKI and elucidate DRD4 as a potential protectant against IRI or cisplatin-induced nephrotoxicity.